Imidazole-Functionalized Y-Shaped Push-Pull Dye for Nerve Agent Sensing as well as a Catalyst for Their Detoxification - Dey, Nilanjan; Kulhánek, Jiří; Bureš, Filip; Bhattacharya, Santanu (American Chemical Society, 2021)
A Y-shaped push-pull dye (1) with N,N-dimethylanilino donors and a benzonitrile acceptor connected via an imidazole-based Jr-conjugated spacer was designed. It showed a dark yellow color in solution due to facile intramolecular charge-transfer interaction, but no fluorescence was detected, presumably due to the photo-induced electron transfer effect of the imidazole moiety. However, addition of nerve agents such as diethyl chlorophosphate (DCP, sarin mimic) and diethyl cyanophosphate (DCNP, Tabun mimic) resulted in a blue-colored fluorescence with fading of the native dark yellow color. Mechanistic studies indicated nucleophilic attack of imidazole at the phosphorus of DCP or DCNP, leading to the formation of a phosphorylated intermediate, which undergoes time-dependent hydrolysis (similar to 24 h) in aqueous medium. This process recovers the free probe (enzyme-like behavior) and releases a less-toxic organophosphate compound as the byproduct. The phosphorylated derivative of 1, formed during such interaction, shows a different electronic behavior, which reduces the extent of charge-transfer interaction as well as nonradiative decay and supports emissive properties. Considering the high sensitivity of 1 towards DCP and DCNP with LOD 35 and 42 ppb, we prepared easy test strips for on-site vapor-phase detection of nerve agents.
Push-pull barvivo tvaru Y na bázi imidazolu jako detektor nervových látek a rovněž jako katalyzátor jejich detoxikace
Keywords: imidazole; push-pull dye; nerve agent; catalyst; detoxification; imidazol; push-pull barvivo; nervová látka; katalyzátor; detoxikace